Antifungal Drug Resistance Profile in Candida sp. as a Cause of Oral Candidiasis: A Scoping Review - Anastasia, Mutiara; Mauli Warma Dewi, Intan; Yunivita, Vycke (Jurnal Kedokteran Brawijaya, 2025)
Candida sp. is renowned for causing oral candidiasis. The prevalence of this disease is around 20-25% and the prevalence can increase in patients with systemic factors (40.2,%). Meanwhile, resistance to antifungal drugs can worsen the prognosis, especially in patients who have systemic risk factors. Therefore, this study aimed to analyze the resistance profile of Candida sp. as a cause of oral candidiasis. The scoping review method was used based on Preferred Reporting Items for Systematic Reviews and Meta-Analyse Extensions for Scoping Reviews. Data were collected through the Pubmed, Springer Open, and Google Scholar databases. Based on the inclusion and exclusion criteria, a total of 18 articles were analyzed. The results showed that antifungal drug resistance test profile depended on the species of Candida and the status of comorbid disease. Based on species, antifungal drug resistance was higher in non-Candida albicans than in Candida albicans. In the comorbid group, Candida sp. resistance to antifungal drugs was higher in the azole group. Meanwhile, in the group without comorbidities, antifungal drug resistance in groups with comorbidities is higher in flucytosine, econazole, and ketoconazole groups than in nystatin, caspofungin, and miconazole. This suggest that the use of nystatin is still effective for treating oral candidiasis. Healthcare provider may need consider prescribing nystatin, especially for patients with systemic risk factors.